ChemInform Abstract: Advancements in Tetronic Acid Chemistry. Part 2. Use as a Simple Precursor to Privileged Heterocyclic Motifs. Issue 50 (November 2016) - Abdou, Moaz M.; El‐Saeed, Rasha A.; Elattar, Khaled M.; Seferoglu, Zeynel; Boukouvalas, John
Abstract: Review: 76 refs.